Makna Culture Shock dalam Komunikasi Lintas Budaya Mahasiswa Indonesia di Luar Negeri - Farah Fadhila; Erik Setiawan (UNISBA Press, 2023)
Abstract. This research was conducted based on the Culture Shock phenomenon experienced by Indonesian students while studying in Germany. This qualitative research uses a phenomenological approach. By using the theory of Anxiety and Uncertainy Management initiated by William Gudykunst. The data in this study were obtained through in-depth interviews with research subjects, namely nine students from Indonesia who were or had studied in Germany and had studied for at least 6 months in Germany. The results of this study show that the motives of Indonesian students to continue their studies in Germany are because they want to learn to live more independently, are interested in learning German language and culture, and get a quality education system. Based on the experiences faced by the research informants, there are several aspects that influence a person experiencing culture shock while living in Germany, including environmental conditions that are different from where they come from, the taste of food in Germany that is different from Indonesia, which ultimately creates a feeling of homesickness. In addition, language skills are considered to be very influential in the process of adapting to a new environment, good language skills make it easier to understand the culture and ethics that apply in their new environment. Through these various experiences of culture shock, each individual gains meaning in the form of the importance of tolerance for cultural differences, motivation for personal life, as well as self-development. Abstrak. Penelitian ini dilakukan berdasarkan dengan adanya fenomena Culture Shock yang dialami mahasiswa Indonesia selama menjalankan studi di Jerman. Penelitian kualitatif ini menggunakan metode pendekatan fenomenologi. Dengan menggunakan teori Anxiety and Uncertainy Management yang dicetuskan oleh William Gudykunst. Data-data dalam penelitian ini diperoleh melalui in-depth interview dengan subjek penelitian, yaitu sembilan orang mahasiswa asal Indonesia yang sedang atau telah menjalankan studi di Jerman dan setidaknya telah menempuh studi minimal selama 6 bulan di Jerman. Hasil dari penelitian ini diperoleh bahwa motif mahasiswa Indonesia melanjutkan studinya ke Jerman dikarenakan ingin belajar hidup lebih mandiri, tertarik mempelajari bahasa serta budaya Jerman, dan mendapatkan sistem pendidikan yang berkualitas. Berdasarkan pengalaman yang dihadapi oleh informan penelitian, terdapat beberapa aspek yang mempengaruhi seseorang mengalami culture shock selama tinggal di Jerman diantaranya karena kondisi lingkungan yang berbeda dengan tempatnya berasal, cita rasa makanan di Jerman yang berbeda dengan Indonesia, sehingga akhirnya menimbulkan perasaan homesick. Selain itu, kemampuan berbahasa dinilai sangat berpengaruh terhadap proses beradaptasi dengan lingkungan baru, kemampuan bahasa yang baik mempermudah untuk memahami budaya dan etika yang berlaku di lingkungan barunya. Melalui berbagai pengalaman culture shock tersebut, masing-masing individu memperoleh makna berupa pentingnya toleransi terhadap perbedaan budaya, motivasi terhadap kehidupan pribadi, serta sebagai self-development.